Pengaruh Digital Marketing dan Market Place terhadap Pendapatan Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Kota Sorong - Andrei Maryen; Lili Sarce Joi Sapari; Felikss Domss Wattimury (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Sorong City has a large number of MSMEs (Micro, Small, and Medium Enterprises) and is growing rapidly. The number of MSMEs in Sorong City is 50 (data source from Bank Indonesia, 2023). The dominant types of businesses are culinary, service, and manufacturing businesses. However, we can still see the existence of established MSMEs struggling to survive. The purpose of this study was to determine the influence of digital marketing and marketplaces on MSME revenues in Sorong City. The research used descriptive quantitative analysis techniques using SPPS software. The results showed that MSME revenues in Sorong City were not significantly impacted by digital marketing and marketplaces.